HUBUNGAN INDEKS MASSA TUBUH DENGAN KELINCAHAN PADA REMAJA USIA 13-15 TAHUN DI SEKOLAH SEPAK BOLA SPARTA LIMO - Abbad Al Wafi, (2023)
Background: Agility is the ability to quickly change position or direction of body movement while moving fast without running out of balance or understanding the orientation of the body position. Body Mass Index (BMI) is very influential in agility because agility plays an important role. Agility is often described as one of the main factors in footballers when on the field and there are also factors that support agility, namely height and weight. The ability of football players while playing to obtain good agility depends on the Body Mass Index (BMI) of each player. Purpose: to find out whether there is a significant relationship between body mass index and the agility of adolescents aged 13-15 years at SPARTA Soccer School. Design: The method used in this research is correlational. The number of samples used in this study were 35 teenagers at SSB SPARTA Limo, Depok. The parameters used in measuring Body Mass Index are Microtoice and Analog Scales and to measure Agility using the Illinois Agility Test. Results: Based on the results of the hypothesis test with spearmen, it was found that the p value <0.05, it can be said that there is a relationship between body mass index and agility in adolescents aged 13-15 years.